IMPLEMENTASI PERATURAN DAERAH NOMOR 19 TAHUN 2009 TENTANG PENGATURAN DAN PELAYANAN AIR MINUM PDAM TIRTA KAMPAR - Candra, Candra; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims to determine how the communication process regarding local regulation number 19 of 2009 on the setting and PDAM Tirta water service Kampar , Is the resource factor has an important role in the regulation and PDAM Tirta water service Kampar and How bureaucratic structure that exists in a number of local regulations 19 of 2009 on the setting and PDAM tirta water service Kampar . Uses resources through informants . In this study, the informant is the Director of PDAM Tirta Kampar , Head of General PDAM Tirta Kampar , Head of Planning PDAM Tirta Kampar , Head of Finance and Public Bangkinang City . While the techniques of data collection consisted of interviews , documentation and observation with the source data consists of primary data and secondary data .From the results of the study showed that the factors that influence in the implementation of Regulation No . 19 FY 2009 is Communication , Resources , Bureaucracy . So it can be concluded that the factors which become obstacles in the implementation of water supply is the Development and implementation of sanctions are less effective and less fair because application of discipline and sanctions unfair , sometimes makes people feel dissatisfied with the performance of PDAM Tirta Kampar and also low public awareness to keep assets such as pipes and taps meter is one of the factors that encourage tight control over water pempenyediaan house and shop in the city Bangkinang . From the research and discussion of PDAM Tirta Kampar in Bangkinang should pay attention to and improve the implementation of existing services . PDAM Tirta Kampar in Bangkinang should be able to provide training to employees for optimal service delivery . So they can follow the operational standards of service .Keyword : PDAM , Regional Regulation , Implementation